Properties of an Emulsion Gel with Gracilaria fisheri Agar, Whey Protein Isolate and Black Seed Oil - Omar, Noorain Nasuha; Ibrahim, Nor Hayati; Mohamad, Nizaha Juhaida; Achudan, Shamini Nair; Amin, Amiza Mat (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2023)
Gracilaria fisheri agar has beneficial potential for human health; however, its application in food products needs to be incorporated into an emulsion gel due to its low gel strength. A response surface methodology with a central composite design was utilized to prepare emulsion gels containing 4–6% Gracilaria fisheri Agar (AGF), 4–8% Whey Protein Isolate (WPI) and 10–20% Black Seed Oil (BSO). The optimum levels of AGF, WPI, and BSO were determined to be 6%, 4% and 10% respectively to give the preferred gel strength of 966.24 g, water holding capacity of 96.12%, and DPPH antioxidant activity of 59.16%.